ANALISIS KEBERADAAN DAN INDEKS KERAGAMAN CENDAWAN MIKORIZA ARBUSKULA (FMA) DI AREAL RHIZOSFER KALAPI (Kalappia celebica Kosterm) PADA DUA LINGKUNGAN TUMBUH YANG BERBEDA DI KABUPATEN KOLAKA - Aminuddin Mane Kandari; Asrianti Arif; Cici Amalia; Safril Kasim (Jurnal Ecogreen, 2016)
The purpose of this research was to know existence and diversity index of Arbuskular Mycorrhiza  Fungi at rhizosfer of kalapi. This research has been done on two growing environment in the Kolaka regency, ie. Pomalaa district and Anaiwoi district, Extraction and spore identification at forestry Laboratory, Faculty of Forestry and Environmental Science., and Soil analyzes at Analytical Chemistry Laboratory, Faculty of Mathematics and Natural Science, Halu Oleo university.  This research was using soil separating method to isolate spore and staining root method to find out root colonization. The observed parameters were type and AMF diversity index.The results showed that (1) the spores of fungi Mycorrhizal Fungi (AMF) associated with the rhizosphere of plants kalapi, where its existence on two different growing environments between natural forests and forest folk Pomalaa Subdistrict Anaiwoi in Kolaka; (2) the main difference of the growing environment kalapi plant area in District Pomalaa and Anaiwoi, namely the condition of vegetation on Pomalaa (Natural Forest) and in Anaiwoi (community forest), altitude Pomalaa (100,97 m dpl) and Anaiwoi (20.25 m dpl ), Pomalaa temperature (27oC) and Anaiwoi (30 °C), humidity Pomalaa 69% and Anaiwoi 64%, the pH of the soil in Pomalaa  6.5 and Anaiwoi 5.4, as well as P-provided Pomalaa 4.45 ppm and Anaiwoi 7, 84 ppm; (3)  The existence of growing FMA in Environmental Natural Forest in District Pomalaa, namely Glomus sp many as six species with 30 Spore, one species Acaulospora sp and one species Gigaspora sp. While in the growing environment of community forests in the district Anaiwoi, namely Glomus sp is nine species with 90 spores, with two spores Acaulospora sp and sp Gigaspora with the spores, each of the species; (4) FMA diversity index in the growing environment in the District Natural Forest Pomalaa lower the 1,547 with low category, compared with the index of diversity on these lands in the District Anaiwoi (1.967) with the medium category. Key word:  Mycorrhiza Fungi, Spore, Growing environment different, diversity index, Kalapi